2015
DOI: 10.1016/j.ijcard.2015.07.099
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide and stroke: A time series study of ambient air pollution and emergency hospitalizations

Abstract: Short-term exposure to ambient CO was associated with decreased risk of emergency hospitalizations for stroke, suggesting some acute protective effects of CO exposure against stroke onsets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 38 publications
2
23
1
Order By: Relevance
“…However, Tian et al (2015) found that low environmental CO was associated with reduced risk of daily stroke hospitalizations [10]. In this study, an almost linear exposure-response relationship of stroke admissions at higher concentrations of CO was observed with a threshold value.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…However, Tian et al (2015) found that low environmental CO was associated with reduced risk of daily stroke hospitalizations [10]. In this study, an almost linear exposure-response relationship of stroke admissions at higher concentrations of CO was observed with a threshold value.…”
Section: Discussionmentioning
confidence: 48%
“…Two-pollutant models adjusting PM 2.5 were fitted to check the modifying effect of PM 2.5 on associations of gaseous air pollutants and stroke admissions. We tested the statistical significance of subgroup differences through Z test [10]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a slightly anomalous result with 125 kg/h CO 2 enhancement at 70kW for which there was also a low standard deviation of 0.14. On the test date all results of CO were 2-3ppm higher than other dates, this may be due to an unusual concentration in the fuel, or more likely there were slightly raised ambient levels of CO, such a value would not be exceptional [24,25].…”
Section: Emissions Impactmentioning
confidence: 82%
“…[66] Consistent with these findings, Tian et al, recently reported a negative association between short-term CO exposure and emergency stroke hospitalizations. [67] By contrast, a recent meta-analysis demonstrated increased hospital admissions secondary to CO exposure. [50] Further study is warranted.…”
Section: Air Pollution and Strokementioning
confidence: 99%